Education through human rights lens: Psychosocial development and student engagement in school - Nuno Archer de Carvalho; Feliciano Henriques Veiga (Contexto & Educação)
The right to education entails a specific quality of education that summons full personality development and educational processes. However, the pressing need for a theoretical framework to address these aspects at the student level, particularly during adolescence, a crucial period for promoting lifelong well-being, thriving, and active participation, cannot be overstated. The study aims to present a theoretical perspective to address full personality development and educational processes at the student level. Following initial considerations, we suggest two sound theoretical and empirical approaches highly relevant to education research: Erikson’s psychosocial development to address full personality development; student engagement in school to address educational processes. For each approach, prospects and challenges are presented. The discussion section focuses on the feasibility of a framework using these approaches to address the right to education at the level of students’ experience. The study presents a practical and constructive framework to actualize the right to quality education and advocates for its significance in both research and intervention. While the perspectives hold promise, this work serves as a starting point for debate and issue presentation. Further empirical endeavors are imperative, given the urgent need to consider education's role in adolescent’s thriving. However, the potential of the presented perspectives gives us hope for the future of education.